An innovative phase II trial to establish proof of efficacy and optimal dose of a new inhaled epithelial sodium channel inhibitor BI 1265162 in adults and adolescents with cystic fibrosis: BALANCE-CFTM 1. Issue 4 (7th December 2020) - Goss, Christopher H.; Jain, Raksha; Seibold, Wolfgang; Picard, Anne-Caroline; Hsu, Ming-Chi; Gupta, Abhya; Fajac, Isabelle
Inhibition of the epithelial sodium channel (ENaC) represents an important, mutation-agnostic therapeutic approach to restore airway surface liquid in patients with cystic fibrosis (CF). A phase II trial of the ENaC inhibitor BI 1265162, inhaled via the Respimat® Soft Mist™ inhaler, in patients aged ≥12 years with CF is being conducted to assess the efficacy and safety of BI 1265162, on top of standard CF treatment (www.clinicaltrials.gov identifier NCT04059094). BALANCE-CF™ 1 is a multinational, randomised, double-blind, placebo-controlled, parallel-group, dose-ranging trial consisting of 2 weeks' screening, 4 weeks' randomised treatment and 1 week follow-up. 98 patients, including ≥21 adolescents, will be randomised. First, 28 patients will be allocated to the highest dose of BI 1265162 (200 µg twice daily) or placebo in a 1:1 ratio. The remaining 70 patients will be allocated to one of five treatment arms (200 µg, 100 µg, 50 µg, 20 µg or placebo twice daily), with a final distribution ratio of 2:1:1:1:2. Recruitment and randomisation will begin with adult patients. An independent data monitoring committee will review safety data to advise on inclusion of adolescents and study continuation. A futility analysis will be conducted after 28 patients to prevent exposure of further patients in case of insufficient evidence of clinical efficacy. The design ensures that potential for effect is assessed ahead of wider enrolment, allowing investigation of a dose–response effect with minimal patient numbers. The results will increase understanding of efficacy, safety and optimal dosing of the inhaled ENaC inhibitor BI 1265162 in adults and adolescents with CF. BALANCE-CF™-1 is an innovative phase II trial in patients aged ≥12 years with CF to assess the efficacy and safety of the inhaled ENaC inhibitor BI 1265162 vs placebo. The results will increase understanding and support further investigation in phase III trials. https://bit.ly/2B8WOPe